Identification of traumatic acid as a potential plasma biomarker for sarcopenia using a metabolomics‐based approach. Issue 1 (22nd December 2021) - Tsai, Jaw‐Shiun; Wang, San‐Yuan; Chang, Chin‐Hao; Chen, Chin‐Ying; Wen, Chiung‐Jung; Chen, Guan‐Yuan; Kuo, Ching‐Hua; Tseng, Y. Jane; Chen, Ching‐Yu
Abstract: Background: The pathogenesis of sarcopenia is complex and has not been well explored. Identifying biomarkers is a promising strategy for exploring the mechanism of sarcopenia. This study aimed to identify potential biomarkers of sarcopenia through a metabolomic analysis of plasma metabolites in elderly subjects (≥65 years of age) vs. younger adults (<65 years of age). Methods: Of the 168 candidates in the Comprehensive Geriatric Assessment and Frailty Study of Elderly Outpatients, 24 elderly subjects (≥65 years of age) with sarcopenia were age and sex matched with 24 elderly subjects without sarcopenia. In addition, 24 younger adults were recruited for comparison. Muscle strength, gait speed, and metabolic and inflammatory parameters, including plasma tumour necrosis factor‐α, C‐reactive protein, irisin, and growth differentiation factor 15 (GDF‐15) levels were assessed. Metabolomic analysis was carried out using the plasma metabolites. Results: Seventy‐two participants were enrolled, including 10 (41.6%) men and 14 (58.3%) women in both groups of elderly subjects. The median ages of elderly subjects with and without sarcopenia were 82 (range: 67–88) and 81.5 (range: 67–87) years, respectively. Among the 242 plasma metabolic peaks analysed among these three groups, traumatic acid was considered as a sarcopenia‐related metabolite. The plasma traumatic acid signal intensity level was significantly higher in elderly subjects with sarcopenia than in elderly subjects without sarcopenia [591.5 (inter‐quartile range, IQR: 491.5–664.5) vs. 430.0 (IQR: 261.0–599.5), P  = 0.0063]. The plasma concentrations of traumatic acid were 15.8 (IQR: 11.5–21.7), 21.1 (IQR: 16.0–25.8), and 24.3 (IQR: 18.0–29.5) ppb in younger adults [age range: 23–37 years, 12 (50%) men], elderly subjects without sarcopenia, and elderly subjects with sarcopenia, respectively, thereby depicting an increasing tendency ( P for trend = 0.034). This pattern was similar to that of GDF‐15, a recognized sarcopenia‐related factor. Plasma traumatic acid concentrations were also positively correlated with the presence of hypertension ( r  = 0.25, P  = 0.034), glucose AC ( r  = 0.34, P  = 0.0035), creatinine ( r  = 0.40, P  = 0.0006), and GDF‐15 levels ( r  = 0.25, P  = 0.0376), but negatively correlated with the Modification of Diet in Renal Disease‐simplify‐glomerular filtration rate ( r  = −0.50, P  < 0.0001). Similarly, plasma GDF‐15 concentrations were associated with these factors. Conclusions: Traumatic acid might represent a potential plasma biomarker of sarcopenia. However, further studies are needed to validate the results and investigate the underlying mechanisms.